Bimbingan Teknis Perancangan Modul Ajar Berbasis Merdeka Belajar dan Terpusat pada Murid - Okta Rosfiani; M Cecep Maman Hermawan; Fauza Rizqiya; Danisa Amalia Sidqi (Yayasan Kawanad, 2022)
Direct teaching is a teaching strategy in which new knowledge and skills are presented by the trainer and followed by the teacher-participant. His Three Principles of the Professional Learning Community (KBP). This means ensuring students are learning, collaborating, and focused on student achievement. These three principles focus on working together to achieve student achievement. Therefore, there is a need to build professional learning community partnerships between scholars (teachers) and teachers (class practitioners) through this service activity. Since the launch of the Education Module (RPP) adopted by the Ministry of Education and Culture last year. This service is conducted in a private school using direct instruction (demonstration). This technical instruction influences the development of teachers' professionalism in their professional competencies. Teachers will ultimately be able to understand new topics and guidelines for independent curricula and appropriately and accurately design self-study and student-centered teaching modules. Be ready to practice in a wider context and content. wide for each class.